Gossypiboma: A Patient’s Decade of Abdominal Presentation as a Sequela of a Forgotten Intraperitoneal Foreign Body - Jotham, Seth; Munisi, Yasin; Magesa, Isabela; Kilasi, Jacqueline (Disease and Health Research: New Insights Vol. 8, 2024)
Background: Gossypiboma is the mass formed as a result of a retained foreign material commonly sponge or gauze that is left accidentally during surgery. It tends to occur in different parts of the body but is more pronounced in the abdominal pelvic cavity, as quite a number of procedures are done on both minimal and open (laparotomy) approach bases. Case Presentation: This is a case of a 52-year-old female who presented with a decade’s history of abdominal pain that started 3 months after an open myomectomy. For the entire time, she has been managed as the case of several other intra-abdominal diagnoses. She was generally stable, an abdominal examination revealed an old midline scar with the tender right abdominal field, and the liver and spleen were not palpable with unballotable kidneys. A contrasted abdominal pelvic Computed tomography scan revealed an 11 by 10 cm low-density mass within a thin enhancing capsule having an attachment to the anterior abdominal wall. Laparotomy was done and the excised mass revealed the features of long-term foreign body containment, scattered necrotic tissues, and foreign body multinucleated giant cells with features of suppurative granulomatous inflammations were all seen on histopathological review. Conclusion: Being a serious post-operative complication, Gossypiboma must be prevented simply by adhering to the existing safe surgical standards.